Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13071-020-04107-0
|View full text |Cite
|
Sign up to set email alerts
|

Cattle gastrointestinal nematode egg-spiked faecal samples: high recovery rates using the Mini-FLOTAC technique

Abstract: Background: Faecal egg count (FEC) techniques are commonly used to detect gastrointestinal nematodes (GINs) in cattle and to determine anthelmintic efficacy/resistance through the faecal egg count reduction test (FECRT). Mini-FLOTAC is one of the techniques recommended for a standardised FEC/FECRT of helminth eggs in cattle. However, only one paper evaluated the recovery rate of GIN eggs by Mini-FLOTAC (compared to McMaster and modified-Wisconsin method) in cattle, using only a level of contamination of 200 eg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The Mini-FLOTAC technique [ 7 ] has been recently demonstrated to be a highly sensitive method for diagnosing parasitic infections of human and veterinary importance where larvae or ova of parasites are shed in the feces [ 8 11 ]. Moreover, the mini-FLOTAC technique in combination with Fill-FLOTAC has been shown to be user-friendly and safe, with a wide diagnostic range.…”
Section: Discussionmentioning
confidence: 99%
“…The Mini-FLOTAC technique [ 7 ] has been recently demonstrated to be a highly sensitive method for diagnosing parasitic infections of human and veterinary importance where larvae or ova of parasites are shed in the feces [ 8 11 ]. Moreover, the mini-FLOTAC technique in combination with Fill-FLOTAC has been shown to be user-friendly and safe, with a wide diagnostic range.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the Mini-FLOTAC and Fill-FLOTAC are able to reduce time and costs of analysis. Moreover, the Mini-FLOTAC technique when compared to other fecal flotation methods showed an overall higher specificity, sensitivity, accuracy, precision, reproducibility, and repeatability for FEC and FECRT of GIN in livestock (9)(10)(11)(12)(13)(14)(15)17). In addition, the Mini-FLOTAC and Fill-FLOTAC are user-friendly devices (i.e., no special equipment such as a centrifuge, or trained technicians are required), so they can be used directly by veterinarians or farmers in the field (pen-side use) (8).…”
Section: Strengthsmentioning
confidence: 98%
“…The main competitor of the Mini-FLOTAC technique in many countries is the McMaster method. However, different comparison studies performed between these two techniques showed that Mini-FLOTAC method is more sensitive, precise and accurate for the FEC and FECRT in livestock (9,(11)(12)(13)(14)(15)17). In UK there are also other competing methods commercially available, the FECPAK and FECPAK G2 , providing specific features such as pen-side digital data recording avoiding the requirement of a laboratory or specific technical skills.…”
Section: Technological Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Modified McMaster method is the most common method used to quantify the GIN infection in sheep, which uses a two-chamber slide to count the eggs per gram and can detect as low as 50 eggs/g. However, this methodology has been shown to have lower sensitivity than Mini-FLOTAV for FEC lower than <500 eggs/g ( Amadesi et al, 2020 ). On the other hand, the Triple Chamber McMaster method uses three-chamber slide to count the eggs per gram and can detect as low as 8 eggs/g.…”
Section: Introductionmentioning
confidence: 99%